A dose-response meta-analysis of green tea consumption and breast cancer risk. (17th August 2020) - Wang, Yanli; Zhao, Yanyan; Chong, Feifei; Song, Mengmeng; Sun, Qiuyu; Li, Tiandong; Xu, Linping; Song, Chunhua
Abstract: Whether drinking green tea (GT) could reduce the risk of breast cancer (BC) is still controversial. The search was performed using PubMed, Embase and Web of Science databases. The generalised least square method and constrained cubic spline model were performed to assess the dose-response trends between GT consumption and BC risk. The attributable risk proportion (ARP) was also calculated. A total of 16 studies were included and the pooled relative risks was 0.86 (95%CI: 0.75–0.99) for BC risk at the highest vs. lowest levels of GT consumption. GT consumption ( p nonlinearity  = .110), drinking GT years ( p nonlinearity  = .393) and BC risk were both negatively linearly correlated. Moreover, The ARP results demonstrated in China, people who drink GT do not suffer from BC, 23.5% of which may be attributed to drinking GT. In conclusion, drinking GT may have a positive effect on reducing BC risk, especially in long-term, high doses.